"In every rank, or great or small, 'Tis industry supports us all": Romanians and ethnic Hungarians, and their wages, in transition - Daniela Andrén (Örebro University School of Business, 2010)
Legally binding treaties or memorandums have been used over time to regulate the issue of national borders of many European countries. As a result, relatively large groups of people have become ethnic minorities in other countries. They may conserve their ethnic identities, and therefore their children may accumulate ethnic human capital (e.g., language, culture, and religion) in addition to the general human capital of the country. Therefore, they can get access to an appropriate occupation linked by tradition or other factors to their ethnic group. This paper uses estimates from a selection model with an endogenous switch among three broad types of occupational groups to analyze the composition of the wage gap between Romanians and ethnic Hungarians in Romania before and during the transition from a planned to a market economy. The results suggest that the institutional settings of the controlled economy allowed Romanians to work in occupations that gave them the best returns, while the changes during the transition years allowed ethnic Hungarians to work in occupations that gave them the best returns.
Keywords: J31; J38; J39; J71; P27; 330; ethnic wage gap; occupation; selection model with an endogenous switch; wage gap decomposition